2019
DOI: 10.1101/556621
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

3D cell culture stimulates the secretion of in vivo like extracellular vesicles

Abstract: For studying cellular communications ex-vivo, a two-dimensional (2D) cell culture model is currently used as the "gold standard". 2D culture models are also widely used in the study of RNA expression profiles from tumor cells secreted extracellular vesicles (EVs) for tumor biomarker discovery. Although the 2D culture system is simple and easily accessible, the culture environment is unable to represent in vivo extracellular matrix (ECM) microenvironment. Our study observed that 2D culture-derived EVs showed si… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 90 publications
1
30
0
Order By: Relevance
“…Most of the studies about EVs from human cells have been made with cell lineages, including HeLa [ 29 , 30 ], THP-1 [ 18 , 31 ], HEK [ 32 , 33 ], HMC-1 [ 34 , 35 ], intestinal cell lines [ 36 ], or brain endothelial cells lines [ 37 , 38 ], and few with primary cells, such as dendritic cells (DCs) [ 39 41 ] or neutrophils [ 42 ]. However, detailed protocol for isolation, characterization, and analysis of interaction with recipient cells of sEVs released by primary human macrophages derived from circulating monocytes are barely available.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies about EVs from human cells have been made with cell lineages, including HeLa [ 29 , 30 ], THP-1 [ 18 , 31 ], HEK [ 32 , 33 ], HMC-1 [ 34 , 35 ], intestinal cell lines [ 36 ], or brain endothelial cells lines [ 37 , 38 ], and few with primary cells, such as dendritic cells (DCs) [ 39 41 ] or neutrophils [ 42 ]. However, detailed protocol for isolation, characterization, and analysis of interaction with recipient cells of sEVs released by primary human macrophages derived from circulating monocytes are barely available.…”
Section: Introductionmentioning
confidence: 99%
“…It should be clarified that the differences between the number of particles/mL and the EV protein concentration are reflecting the measurement of any particle isolated by ultracentrifugation in comparison to the actual protein measurement. Enhanced secretion of EVs in 3D models has previously been reported [ 67 ]. Finally, human plasma was found to be an excellent reservoir for cytokines involved in key cancer hallmarks including: pro-inflammatory cytokines (IL-β1, MIP-1a, TNFα, and RANTES) [ 68 , 69 ], chemokines influencing the invasiveness and migration (SDF-1) [ 70 ], cytokines supporting tissue repair/ECM degradation and remodeling (TIMP1, TIMP2, MMP1, and MMP9) [ 71 , 72 ], and cytokines promoting cell growth (INF-γ, PDGF-AB, IL-2, and LIF) [ 69 , 73 ].…”
Section: Discussionmentioning
confidence: 86%
“…However, the majority of studies elucidating EVs composition and hence their mechanism of action, isolate these nanoparticles from 2D TCP, a highly artificial system compared to the cells’ native microenvironment [ 139 ]. For example, Thippabhotla et al demonstrated that EVs derived from cervical cancer cells cultured on TCP displayed a significantly altered RNA and DNA content when compared to that of EVs derived from 3D models, with the later exhibiting ~96% RNA similarity to in vivo derived EVs (compared to ~80% similarity of TCP derived EVs) [ 140 ]. Improving the biomimicry of EVs isolated from in vitro systems allows for more accurate native replication using various engineering strategies utilised.…”
Section: Ev-functionalised Biomaterialsmentioning
confidence: 99%